The Role of Networks and Social Capital for Street Vendors on Jl. Laut Dendang, Deli Serdang Regency - Widya Pangestika; Annisa M Nasution; Faris Al Hakim; Irwansyah P Marpaung; Nurhotma Tambak; Riski Ihsan (Pena Cendekia Insani, 2021)
Networks and social capital act as a binder for everyone in society. Social capital is an important issue because an economic business will be successful not only with financial capital, but also with the need for support from human resources, and social capital is one of its elements. Social capital refers to the main aspects of social organization such as trust, norms, networks, which are able to mobilize the participation of group members to achieve common goals. The street vendor who sells vegetables on the Dendang Sea Transportation Road is one of the street vendor communities in Deli Serdang Regency, which has survived in its business. The purpose of this study is to find out how trust is formed among street vendors, especially street vendors of vegetables on Jalan Laut Dendang and to find out the reciprocal relationship between street vendors on Jalan Laut Dendang. This type of research is descriptive qualitative, then the sample is based on purposive sampling technique (purpose sample) and 5 street vendors are determined. Analysis Techniques Data were analyzed qualitatively, based on theoretical support related to the object of research from respondents by means of observation and interviews. Then a conclusion is drawn regarding the results of the study. The main aspects of social capital that refer to trust, norms and networks that are seen in the vegetable street vendors (PKL) on the Dendang Sea Transportation Road show the value of social capital that is formed and interwoven between traders from the rules and regulations. Informal rules that apply in the merchant group they are able to obey together, even though there is no written agreement, so that these informal rules become separate norms that develop and are implemented together, reflecting the spirit of mutual giving, mutual trust, and the existence of networks. social network.